2015
DOI: 10.1016/j.cedpsych.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of place in school-based intervention research

Abstract: The commentary made here by this intervention researcher arises from a "place" in which schoolbased interventions are used to build knowledge, and thereby to bring relief to a young democracy -at once highly diverse and in transition -with aspirations for eradicating inequality. I use the concept of place as a theoretical lens to argue that intervention researchers, whose task it is to consider the meaning of intervention findings in different contexts, require a cognisance of pluriversality and geopolitical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 70 publications
3
4
0
Order By: Relevance
“…Schleicher (2015) reported that teachers in Indonesia attending teacher development program of which district office and the school supervisors involved feel more confident and better prepared. These findings are consistent with Ebersöhn et al (2015) who find that school intervention for in-service teachers in highrisk and high-need schools in South Africa motivated teachers to gain competency and optimism, demonstrate management skills, and make valuable contributions in a group.…”
Section: Introductionsupporting
confidence: 89%
“…Schleicher (2015) reported that teachers in Indonesia attending teacher development program of which district office and the school supervisors involved feel more confident and better prepared. These findings are consistent with Ebersöhn et al (2015) who find that school intervention for in-service teachers in highrisk and high-need schools in South Africa motivated teachers to gain competency and optimism, demonstrate management skills, and make valuable contributions in a group.…”
Section: Introductionsupporting
confidence: 89%
“…It will be interesting to see anti-IL-17 data in non-radiographic axial spondyloarthritis, and to learn more about the relative effect of IL-17 inhibition in patients with and without an increased C-reactive protein concentration at baseline. 10 Finally, similar to previous studies, the expectation is that the efficacy of ixekizumab will also be sustained over several years with relatively high retention and limited radiographic progression. 10,11 Nevertheless, there is still an unmet need for head-tohead and strategy trials to provide better and scientifically based care to patients with axial spondyloarthritis.…”
supporting
confidence: 52%
“…Rather, as the science of learning has evolved, intervention researchers have begun to blend or weave the theoretical roots emanating from various traditions to maximize the effects of an instructional intervention on students’ learning as it unfolds in the multidimensional, dynamic nature of actual classrooms. There are numerous examples of this type of intervention: that is, intervention that draws on the very best of what is known about the science of learning across the various lenses (e.g., Flourishing Learning Youth, see Ebersöhn, 2015; Self-Regulated Strategy Development, see Harris et al, 2012; Quality Talk, see Murphy, Greene, & Firetto, 2015). What is articulated by Murphy (2015) and others (e.g., Greene, 2015; Harris, Graham, & Adkins, 2015; Star et al, 2015) in a recent special issue of Contemporary Educational Psychology is that the sustainability of instructional innovations rests in their feasibility and usefulness as well as their adaptability.…”
Section: Implications For Teaching and Instruction Through Epistemic mentioning
confidence: 99%
“…What is articulated by Murphy (2015) and others (e.g., Greene, 2015; Harris, Graham, & Adkins, 2015; Star et al, 2015) in a recent special issue of Contemporary Educational Psychology is that the sustainability of instructional innovations rests in their feasibility and usefulness as well as their adaptability. In essence, each classroom is a unique place where many factors are at play, including the teacher, students, administrators, and parents, and each of these stakeholders plays a role in determining how learning will unfold (Ebersöhn, 2015). Thus, it is fundamental that instructional interventions must address the challenges faced by sociocultural groups in particular contexts, while simultaneously nurturing behavior, motivation, and cognition.…”
Section: Implications For Teaching and Instruction Through Epistemic mentioning
confidence: 99%